Kegiatan Perlombaan Keagamaan bagi Anak-Anak: Upaya Meningkatkan Kepercayaan Diri Siswa Mengikuti Perlombaan - Manurung, Purbatua; Jannah, Lu'lu' Ul; Tanjung, Khofifah; Kurniati, Marini; Siregar, Masdura; Maslan, Maslan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the factors that can affect a child's lack of confidence is an unsupportive environment. From the religious competition held in Lalang Village, it was apparent that some children lacked confidence when participating in religious competitions. Lack of skills can also be a cause of a child's lack of confidence. Therefore, motivation from parents and support from the environment are very important for the development of a child's confidence. Confidence is an attitude or belief in one's own abilities. One way to boost a child's confidence is through group guidance. Through group guidance activities, individuals can experience positive changes or effects. It is proven that students' confidence increases after participating in group guidance.